Design and Experimental Validation of a Cooperative Driving System in the Grand Cooperative Driving Challenge - Kianfar, Roozbeh; Augusto, Bruno; Ebadighajari, Alireza; Hakeem, Usman; Nilsson, Josef; Raza, Ali; Tabar, Reza S.; Irukulapati, Naga VishnuKanth; Englund, Cristofer; Falcone, Paolo; Papanastasiou, Stylianos; Svensson, Lennart; et al. (IEEE transactions on intelligent transportation systems, 2012)
In this paper, we present the Cooperative Adaptive Cruise Control (CACC) architecture, which was proposed and implemented by the team from Chalmers University of Technology, Göteborg, Sweden, that joined the Grand Cooperative Driving Challenge (GCDC) in 2011. The proposed CACC architecture consists of the following three main components, which are described in detail: 1) communication; 2) sensor fusion; and 3) control. Both simulation and experimental results are provided, demonstrating that the proposed CACC system can drive within a vehicle platoon while minimizing the inter-vehicle spacing within the allowed range of safety distances, tracking a desired speed profile, and attenuating acceleration shockwaves.